SENSORY VOCABULARY IN MULTIMODAL DIGITAL BRAND STORYTELLING (BASED ON THE ENGLISH–LANGUAGE WEBSITES AND SOCIAL MEDIA) - Kiriakova, Daria (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2025)
This article investigates the use of sensory vocabulary within multimodal digital brand storytelling, analysing how linguistic choices, in conjunction with visual, auditory, and interactive elements, contribute to brand perception and consumer engagement. Employing a mixed–methods approach, we combine multimodal and contextual discourse analysis with quantitative data and empirical observations of brand websites and social media content. We have analysed how leading brands across industries, including spheres such as technology, cosmetics, and food and beverage, utilise sensory language, in conjunction with visual, auditory, and interactive modes, to construct compelling digital narratives. Findings reveal that the effective integration of sensory vocabulary significantly enhances brand perception by creating immersive and emotionally resonant experiences, tailored to specific product offerings and brand identities. The article reveals usage of distinct sensory strategies, demonstrating the importance of contextual factors and the complex interplay of multimodal elements. Furthermore, the study underscores the emotional impact of sensory language, particularly in fostering brand loyalty and consumer engagement, highlighting the connection between tactile descriptions and emotional narratives. This research contributes to a deeper understanding of digital brand communication, offering insights for strategic sensory storytelling and digital branding, and provides a framework for future research into the evolving landscape of digital sensory marketing._____________References:• Belova, A. (2021). Storytelling in advertising and branding. Cognition, Communication, Discourse, (22), 13–26. https://doi.org/10.26565/2218–2926–2021–22–01• Belova, A. (2024). Multisensory perception of exotic fruits and flavour conveyability in English. Cognition, Communication, Discourse, (28), 7–23. https://doi.org/10.26565/2218–2926–2024–28–01• Cascio Rizzo, Giovanni Luca & Berger, Jonah & Deangelis, Matteo & Pozharliev, Rumen. (2023). How Sensory Language Shapes Influencer’s Impact. Journal of Consumer Research. https://doi.org/50. 10.1093/jcr/ucad017.• Değermen Erenkol, Anıl. (2015). Sensory Marketing. Journal of Administrative Sciences and Policy Studies. 3. 1–26. https://doi.org/10.15640/jasps.v3n1a1• Le, Nguyen & Mai, Ngoc & Nguyễn, Như Ý & Vu, Huyen. (2024). Multi–Sensory Marketing and Impulsive Buying Behavior: The Role of Impulsive Buying Traits. Emerging Science Journal. 8. 1764–1782. https://doi.org/10.28991/ESJ–2024–08–05–05• Lindstrom, Martin. (2006). Brand Sense: How to Build Powerful Brands Through Touch, Taste, Smell, Sight and Sound. Strategic Direction. 22. https://doi.org/10.1108/sd.2006.05622bae.001• Longley, Robert. "An Introduction to Sensory Marketing." ThoughtCo. https://www.thoughtco.com/sensory–marketing–4153908 (accessed March 15, 2025).• McLellan, Hilary. (2006). Digital Storytelling: Bridging Old and New. Educational Technology, 46(5), 26–31. JSTOR. URL: http://www.jstor.org/stable/44429328. Accessed 22 Aug. 2024.• Pareek, Richa & Kumari, Lalita & Mongia, Anupal & Sharma, Meena. (2024). Sensory Marketing and Its Influence on Consumer Buying Behavior: A Comprehensive Analysis. https://doi.org/10.4018/979–8–3693–9351–2.ch008• Yltävä, L. "Share of Global Internet Users Who Primarily Used the Following Channels When Looking for More Information about Brands in 2023." Statista. URL:https://www.statista.com/statistics/1455056/online–channels–for–brand–information–search–worldwide/#statisticContainer (Accessed March 19, 2025)Sources:• Apple official Instagram account: https://www.instagram.com/apple?igsh= YTcyeHd6MDFtYzdr• Apple official website: https://www.apple.com/• Coca–Cola official Instagram account: https://www.instagram.com/cocacola?igsh= MTg1YXpvYXB3ZnI5Zg==• Coca–Cola official website: https://www.coca–cola.com/us/en/brands/coca–cola• Dove official Instagram account: https://www.instagram.com/dove?igsh=MWs3Ymxla XlnbzRpOQ==• Dove official website: https://www.dove.com/uk/home.html• How to Arouse the Magic of Sensory Words (+ 75 Example Phrases): https://www.enchantingmarketing.com/sensory–words/• L’Oreal official Instagram account: https://www.instagram.com/lorealparis?igsh= Z2NzdjZ5OHNwanMz• L’Oreal official website: https://www.lorealparisusa.com/• Learning Resource Center – Writing Center: https://www.msjc.edu/ learningresourcecenter/documents/writing–handouts/grammar/WC–Sensory–Words.pdf• Samsung official Instagram account: https://www.instagram.com/samsung? igsh=MWY4YzJ5MXZscTZ4cw==• Samsung official website: https://www.samsung.com/uk/• Starbucks official Instagram account: https://www.instagram.com/starbucks? igsh=bTV6MGs5cWlmaDJ1• Starbucks official website: https://about.starbucks.com/
Keywords: sensory vocabulary, sensory marketing, multimodality, storytelling, digital communication, narrative, social media, marketing